The gold mines of Costa Rica - Reitz, Milton Franklin (Universidad de Costa Rica, 2011)
Like the mines of every other part of the writer has spent two years immediately connected world, something have been said and written of with the mines of the country and has personally vi- those in this republic. All connected with the mi- sited the more important properties here mentioned. ning industry know the nature and effect of such Physical conditions notes are given from personal writings. It is a well-known fact that the press knowledge, and are corroborated by reports made throughout the States have given space to reviews at various times by eminent engineers. Statistical of this sort relative to all known mining districts, facts observed are taken from original mint retur- the authenticity of which has not always been ns, assay certificates, and bills of sale now in the without question. This articles in many instances file of the owners of the mines. As there is proba- have been produced by special reporters, who bly no bet er way of judging the future than by the have spent limited time in their preparation, with past, I have thought it of interest to give some his- the prime purpose of obtaining readable matter, tory, especial y with reference to the mines of the and with the result that facts have been sacrificed Aguacate Mountain, for which I am indebted to to give due credit to the legends and traditions met Don Francisco María Yglesias, who, with his father with in all mining communities.